How Have the CAP Reforms Contributed to Structural Development in Agriculture? - Kyösti Arovuori (Wieś i Rolnictwo)
This study aims to analyse the impact of the Common Agricultural Policy and its reforms on the development of agricultural structures. In the analysis we measure the development of rural structures using the number of farms as policy target variable. Our analysis aims to reveal the impact of agricultural policy and policy reforms on the development of the defined target variable, given the general economic and structural development. The analysis is conducted as an econometric panel data analysis. Our results show that agricultural policies have, in general, reduced the pace of structural development and kept more farms in the sector compared to a situation without policies. However, the implementation of CAP reforms in 1992, 2000 and 2007 has led to more rapid structural development. Overall, agricultural policies have smoothened the transition of resources from agriculture to other sectors.